TABU DALAM KEHIDUPAN MASYARAKAT INGIN JAYA ACEH BESAR - Muhammad Chaizir (Abrahamic Religions: Jurnal Studi Agama-Agama, 2021)
Taboo is something forbidden to do which is still believed and practiced within the community even though people already live in the modern world and face globalization. Belief on taboo has long since existed from one generation to another. This study aimed to describe taboos in the community life of the people in Ingin Jaya Sub-district, Aceh Besar District. The study used field research approach with the qualitative method. The primary source of data came from interview, observation, and documentation. Library research was also carried out to support the data. The findings showed that the people of Ingin Jaya still believe various types of taboos. There are taboos involving hard and sharp objects such as prohibition in buying nails, needles, any hard/metal objects, and salt at night, prohibition in sitting under the stairs or at the door, and prohibition in sleeping under the open sky or no roof. The belief on taboos occurs due to two factors. The internal factors include family, education, and religious knowledge, while the external factor includes the socio-culture of the community which exists over generations. The community’s belief on taboos affects the people’ religious experiences in which the people tend to feel comfortable, safe, and secure whenever they follow the social rules by not violating those taboos.